The mental map as an instrument to define indicators in complex systems: an application on the environmental knowledge of local horticultural farmers - Blandi, María Luz (2022)
The reductionist and disciplinary paradigm of the Green Revolution coexists with the emerging paradigm of complexity, which values ​​the holistic and the interdisciplinary. Agroecology promotes the need to understand the multiple biophysical relationships that exist in agroecosystems, and this calls for the development of new methodological tools. Sustainability indicators are an example of this. However, their implementation is not simple, as this requires an instrument to simplify the construction of such indicators. The objective of this work is to use the “mental map” as a guide for the development and application of indicators. The graph follows the conceptual path that facilitates the understanding of the variable and its breakdown into smaller and measurable units of analysis, i.e. the indicators. The created mental map has two stages: the development of indicators and their application. Its utility is presented in a case study that addresses local environmental knowledge (LEK). The results of this work show that complexity can be translated into quantifiable, measurable, and comparable variables, without this representing the loss of its characteristics. In addition, it proves that the created tool facilitates the evaluation and understanding of the functioning of agroecosystems, which contributes to decision-making.